2000
DOI: 10.1093/geront/40.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Negative Consequences of Hearing Impairment in Old Age

Abstract: To determine whether functional and psychosocial outcomes associated with hearing impairment are a direct result or stem from prevalent comorbidity, we analyzed the impact of two levels of reported hearing impairment on health and psychosocial functioning one year later with adjustments for baseline chronic conditions. Physical functioning, mental health, and social functioning decreased in a dose-response pattern for those with progressive levels of hearing impairment compared with those reporting no impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
273
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(307 citation statements)
references
References 29 publications
20
273
1
6
Order By: Relevance
“…It is encouraging that psychosocial talk was a focus of one quarter of the history taking phases observed in the current study, given that psychosocial talk is often not a focus of physician-patient interactions in primary health care [14,[30][31][32]. However, given that adults with acquired hearing loss typically attend an audiology appointment because they are experiencing communication difficulties [17,33] and thus may have experienced changes to their lifestyle (e.g., withdrawing from social situations) and/or general well-being [34][35][36][37][38][39], one would expect a greater proportion of audiology appointments to begin with psychosocial interaction.…”
Section: Discussionmentioning
confidence: 92%
“…It is encouraging that psychosocial talk was a focus of one quarter of the history taking phases observed in the current study, given that psychosocial talk is often not a focus of physician-patient interactions in primary health care [14,[30][31][32]. However, given that adults with acquired hearing loss typically attend an audiology appointment because they are experiencing communication difficulties [17,33] and thus may have experienced changes to their lifestyle (e.g., withdrawing from social situations) and/or general well-being [34][35][36][37][38][39], one would expect a greater proportion of audiology appointments to begin with psychosocial interaction.…”
Section: Discussionmentioning
confidence: 92%
“…34,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Of particular concern for rehabilitation providers are studies that find depression is more prevalent among persons with dual loss than those with single impairments in vision or hearing. For example, among community-dwelling older individuals with objective assessments of sensory function (ie, Snellen acuity and free-field voice testing), visual and hearing impairments increased the odds of depression by 2.3 and 1.8, respectively.…”
Section: Dual Sensory Loss and Psychological Functionmentioning
confidence: 99%
“…Several studies have reported that older adults who are hearing impaired have greater functional disability when compared with their nonimpaired peers [10,12,15,18,[26][27][28]. However, this relationship does not appear to be as strong when compared with the relationship between visual impairment and ADL/IADL disability [25,[29][30].…”
Section: Hearing Impairmentmentioning
confidence: 99%